The effect of PCOS status on atherosclerosis markers and cardiovascular disease risk factors in young women with vitamin D deficiency - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2021)
Objective To investigate whether polycystic ovary syndrome (PCOS) had further deteriorating influence on endothelial function or cardiometabolic parameters in women with vitamin D deficiency during reproductive age. Study design The study group was composed of women with PCOS and vitamin D deficiency and insufficiency between the ages of 18 and 35 years. Age and body mass index (BMI)-matched women were chosen as controls. Serum 25(OH) Vit D levels below 20 ng/mL were considered as vitamin D deficiency. The cutoff level of vitamin D insufficiency was suggested at 30 ng/mL. Serum FSH, LH, estradiol, testosterone, DHEA-S, fasting glucose, total cholesterol, HDL, LDL, triglyceride levels were analyzed. Carotid artery intima-media thickness (CIMT) was measured, and the flow-mediated vasodilation (FMD) was calculated. Results CIMT and FMD values in both vitamin D deficiency and insufficiency subgroups showed no significant difference between PCOS and non-PCOS groups. There was a weak negative correlation between BMI, waist/hip ratio, CRP, and 25(OH) Vitamin D. Conclusion PCOS is a heterogeneous disease with different combinations of the diagnostic components. Vitamin D is an important variable for a healthy cardiovascular system. We did not find any difference in early atherosclerotic markers and cardiometabolic features between PCOS and non-PCOS group with Vitamin D deficiency.
Keywords: PCOS; vitamin D deficiency; vitamin D insufficiency; CIMT; FMD; POLYCYSTIC-OVARY-SYNDROME; ENDOTHELIAL FUNCTION; INSULIN-RESISTANCE; D SUPPLEMENTATION; METABOLIC DISTURBANCES; ANDROGEN LEVELS; METAANALYSIS; DIAGNOSIS